What Determines Consumers’ Intention for Hotel Bookings through Smartphone Apps? - Suman Lata (ASEAN Journal on Hospitality and Tourism, 2021)
In the emerging market, the usage of smartphone apps is playing an imperative role and supporting travelers in their online hotel bookings. This study aims to examine the various determinants that affect travelers’ behavioral intention regarding hotel booking through smartphone apps. Data was collected from 379 hotel guests who used smartphone apps for hotel bookings. The respondents for this study are taken from Delhi. Further, the hypotheses of this study were validated with the help of structural equation modeling (SEM) using partial least squares (PLS). The results of this study found all dimensions significant except for effort expectancy, facilitating conditions, and habits. A newly added dimension, perceived trust was also found a significant predictor of consumers’ behavioral intentions for hotel booking through smartphone apps. The study provides implications for hotel managers that the information provided on apps must be accurate, up-to-date, and reliable regarding hotel services. By incorporating relevant information in the system, travelers’ will feel the hotels are trustworthy and thus their tendency to use smartphone apps for hotel bookings will increase.  As well as hotel apps must be easy to operate which reduces travelers' extra efforts and time while using them.